Math, asked by sashank200555, 10 months ago

plz slovve by substitution method ​

Attachments:

Answers

Answered by Anonymous
9

i) √2x + √3y = 0 .....(i)

√3x - √8y = 0 ......(ii)

Let us consider the Equation (ii)

√3x - √8y = 0

x = √8y/√3 ......(iii)

Put the value of x = √8y/√3 in Equation (i),

√2 x √8y/√3 + √3y = 0

√16y + 3y = 0

y(√16 + 3) = 0

y = 0 , x = 0

ii) 3x/2 - 5y/3 = -2 .....(i)

x/3 + y/2 = 13/6 ......(ii)

Let us consider the Equation (ii)

x/3 + y/2 = 13/6

x/3 = 13/6 - y/2

x = 3(13 - 3y)/6

x = (13 - 3y)/2 ......(iii)

Put the value of x = (13 - 3y)/2 in Equation (i),

4 + y + y = 14

2y = 14 - 4

2y = 10

y = 10/2

y = 5

Put the value of y = 5 in equation (i)

x + 5 = 14

x = 14 - 5

x = 9, y = 5

keep smiling ❣️

Similar questions